Synthesis, application and kinetic modeling of CeOx–Si–CoMo catalysts for the hydrodesulfurization of dibenzothiophene. Issue 4 (4th February 2019) - Tanimu, Abdulkadir; Ganiyu, Saheed A.; Adamu, Sagir; Alhooshani, Khalid
Abstract : CeO x –Si–CoMo catalysts for efficient hydrodesulfurization (HDS) activity of dibenzothiophene: role of ceria in catalyst activity and product selectivity. Abstract : The ultradeep hydrodesulfurization (HDS) of fuel with a highly robust catalyst is one of the targets of petroleum refiners to achieve a clean and safe environment. We report in this study a series of CeO x –Si–CoMo catalysts for the efficient HDS activity of DBT in a batch reactor. The dispersion and catalytic activity of the active species (CoMoS) is greatly influenced by the CeO x –Si network in the support, and the structural reactivities of the catalysts are extensively studied. The BET surface area, X-ray diffraction (XRD) and Raman spectroscopy results showed that up to 2.5 wt% Ce incorporated into the silica network of SBA-15 demonstrated the optimum support properties. The ease of metal oxide reducibility and the existence of the MoS2 phase in the sulfided 2.5CeO x –Si–CoMo catalyst revealed that moderate metal–support interactions between the active metals and the supports are achieved at 2.5 wt% ceria, which resulted in higher HDS activity. The HDS and hydrogenation (HYD) rate constants for the 2.5CeO x –Si–CoMo catalyst were the largest compared to the rate constants of other catalysts, indicating higher catalytic activity. The 2.5CeO x –Si–CoMo catalyst directed the HDS reaction towards the HYD pathway more than the other catalysts.